An Aqueous Extract of Ilex paraguariensis Reduces Carrageenan-Induced Edema and Inhibits the Expression of Cyclooxygenase-2 and Inducible Nitric Oxide Synthase in Animal Models of Inflammation - Schinella, Guillermo; Neyret, Elisa; Cónsole, Gloria; Tournier, Horacio; Prieto, José M.; Ríos, José-Luis; Giner, Rosa María (Planta Medica, 2014)
Mate (Ilex paraguariensis) is a highly popular herbal beverage in South America due to its high content of caffeine. Its hypolipidemic and antioxidant properties are of increasing interest in the treatment of cardiovascular disorders and for weight control. In the present study, we show for the first time both the local and systemic anti-inflammatory effects of an aqueous extract of mate in three classic in vivo models, namely acute and chronic 12-O-tetradecanoylphorbol 13-acetate-induced mouse ear edema and acute carrageenan-induced mouse paw edema. Caffeine, rutin, chlorogenic acid, 3,5-dicafeoyl quinic acid, and 4,5-dicafeoyl quinic acid, accompanied by a complex mixture of other simple phenolic acids, were identified in the extract by HPLC-UV analyses. In the acute edema model, mate extract applied topically (1 mg/ear) halved the 12-O-tetradecanoylphorbol 13-acetate-induced acute edema (50 %) and almost suppressed neutrophil infiltration (93 %), while in the 12-O-tetradecanoylphorbol 13-acetate-induced subchronic inflammation, the edema was significantly reduced by 62 % (1 mg/ear/day × seven doses). The oral administration of the mate extract (250 mg/kg) significantly reduced the carrageenan-induced edema at all time points, an effect which was accompanied by a 43 % and 53 % reduction of the expression of cyclooxygenase-2 and inducible nitric oxide synthase, respectively. Histological analyses confirmed a reduction of epithelium thickness, dermis with mild inflammation, hair follicles with some secretory cells of sebaceous glands, and hypodermic adipocytes. In conclusion, mate is endowed with in vivo preventative or therapeutic anti-inflammatory effects in both local and systemic inflammatory processes.
Keywords: Ilex paraguariensis; Aquifoliaceae; mate; anti-inflammatory effects; in vivo